RANCANG BANGUN SISTEM INFORMASI PEMBELAJARAN MENGGUNAKAN UCD DENGAN FITUR MONITORING PADA YAYASAN AMAL SHALEH MEDAN - Rizky Khairuna; Aninda Muliani Harahap (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The rapid advancement of information technology has significantly impacted various aspects of life, including the field of education. This study was conducted at Amal Shaleh Junior High School in Medan, where the learning process was still managed manually, making it difficult for both parents and the school to comprehensively monitor students' academic progress. The research aimed to design and develop a school learning information system to monitor student learning processes at the Amal Shaleh Medan Foundation, using the User-Centered Design (UCD) method. The UCD approach was employed to ensure the system met user needs by following stages that included understanding the user context, identifying user requirements, designing solutions, and evaluating the design. The results of this study can assist the school in facilitating the monitoring of student progress and foster a learning process that is effective, efficient, and oriented toward user needs.